A case report of male breast cancer in a 14-year-old patient - Dewi, Pande Ayu Kirana; Raditha, I. Nengah (International Journal of Research in Medical Sciences, 2021)
Breast cancer is one of the most common malignancies. This malignancy can originate from the epithelium of the ducts or lobules of the breast. Although rare, breast cancer can also be found in men. The incidence of breast cancer in men is <1% of the total breast cancer and it is estimated that 1 in 100.00 men worldwide is diagnosed with breast cancer. Breast cancer in pediatric patients is rare. Incidence of breast cancer in pediatric is estimated to be 0.2-0.8/100.000 for females with less than 20 years old. In this case report is a 14-years-old male with ten years history of a mass in his right breast. At first the mass was said to be as small as a marble, then since last year the mass have grown bigger. Biopsy and histopathology examination were performed to confirm the diagnosis. The result of histopathology examination was ductal invasive carcinoma. The patient and family refused to undergo chemotherapy. The incidence of breast cancer in pediatric is rare, and it has high mortality rate in pediatric patient.